Enhancing Maternal Health Literacy for Stunting Prevention: A Systematic Review of Effective Approaches and Strategies - Amalia, Risa Nur; Nur Alam Fajar; Anita Rahmiwati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Stunting is a global health problem with a significant impact on the physical and cognitive development of children, particularly in developing countries. Health literacy, defined as an individual's ability to understand and utilize health information, plays an important role in preventing stunting. Low health literacy in many developing countries hampers the effectiveness of stunting prevention measures. Objectives: This study explores the roles, approaches, and effective strategies of health literacy in stunting prevention through a systematic review using the PRISMA method. Method: Data were collected from scientific databases such as Scopus, PubMed, ScienceDirect, Emerald Insight, and Taylor & Francis, using keywords including “health literacy,” “stunting,” “stunting prevention,” “approach,” and “strategy.” The articles included in the study were published between 2020 and 2024. Out of 4,126 identified articles, nine met the inclusion criteria and were further analyzed. Results: Maternal health literacy significantly improved understanding of child nutrition, exclusive breastfeeding practices, and growth monitoring. Cultural, community, and technology-based approaches—including digital education through social media—proved effective in enhancing health literacy. Key barriers included limited access to information, low education levels, and cultural norms that challenged implementation. Cross-sector collaboration among government, health workers, and communities is crucial to ensuring sustainable strategies. Conclusion: Health literacy plays a vital role in preventing stunting. Community- and technology-based interventions tailored to local contexts have been effective in improving maternal health knowledge and practices. Implementing health literacy programs can support the achievement of national and global targets for stunting reduction.